Oral Narratives in the Tazkarehalsha'ra of the Dawlatshah Samarghandi - Ghahreman Shiri; Minoo Mohammadi (تاریخ ادبیات, 2019)
The Tazkareh of the Dawlatshah Samarghandi (896 AH) is the most exceptional poet's Tazkareh in Iranian history and literature, despite of the fact that he has had many historical mistakes, the most information about the poets and their period of life with the most traditional methods used in the past to the audience of supply he has done. The study of the particular style of Dawlatshah Samarkandi's, the importance of his strategy in introducing poets by providing the necessary historical descriptions of the clans of their era and the role of the sultans in the intellectual and artistic positions of each poet, the understanding of how to provide information about the memoirs of the poets, the study of the factors of acceptance of Tazkareh al-Sha'ra There are many historical mistakes and issues of this type. The research method is descriptive-analytic and the results are analyzed using content analysis method. results show: Far from any exaggeration and hyperbole it can be argued that this is the most innovative poetic tale in Persian, the author of which did not just seek to provide collection of names and examples of Persian poetry poems, but it has tried every Putting a poet in the historical context of the era from which he originated, to better assess his intellectual and artistic position. This is because the Tazkareh of the Dawlatshah, in addition to the report of the life of the poets, which is the main function of such books, has received a brief summary of most of the ruling dynasties and local governments in different regions of Iran.